Work Life Balance Sebagai Prediktor terhadap Work Engagement pada Karyawan yang Belum Menikah - Asri Nur Ubay; Diah Zaleha Wyandini; Anastasia Wulandari (Universitas Negeri Makassar, 2023)
The purpose of this study was to test empirically the effect of work life balance on work engagement in unmarried employees in Bandung. This study used a correlational method with an unknown population size. Sample selection was carried out using accidental sampling so that a total sample of 422 people was obtained. Data collection was carried out using the WLBS (Work Life Balance Scale) and UWES (Utrecht Work Engagement Scale) measuring instruments. The data analysis technique used is a simple linear regression test. The results of this study indicate that the work life balance variable has a positive and significant effect on work engagement.